2015
DOI: 10.1155/2015/947623
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Toxicity Profile of Lacidipine Nanoformulation in Wistar Rats

Abstract: The present study was aimed at investigating the safety of Lacidipine (LCDP) loaded nanostructured lipid carriers (NLCs) in Wistar rats. NLCs were formulated using ultrasound dispersion technique. Animals were orally treated once daily with NLCs containing 0.140 mg, 0.350 mg, and 0.875 mg of LCDP as low, medium, and high dose per kg body weight, respectively, during 28 days along with blank formulation and pure LCDP. Control rats were fed with water. Animals were observed throughout experiment period and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Both sub-acute and chronic toxicity studies indicated normal serum creatine and urea values, a share painter of non-nephrotoxicity. This is in agreement with the study by Shirodkar (2015). The kidney gross pathology and histological organization appeared normal generally.…”
Section: Discussionsupporting
confidence: 93%
“…Both sub-acute and chronic toxicity studies indicated normal serum creatine and urea values, a share painter of non-nephrotoxicity. This is in agreement with the study by Shirodkar (2015). The kidney gross pathology and histological organization appeared normal generally.…”
Section: Discussionsupporting
confidence: 93%
“…Additional AST enzyme will be released into the bloodstream when liver is damaged that indicates a hepatic injury in the host ( Sharma & Shukla, 2011 ). ALT level is a main indicator in the detection of liver damage by drug or hepatotoxins in the bodies ( Shirodkar et al, 2015 ). Eventually, the increase is AST level caused an elevation in the level of ALT ( Giannini, Testa & Savarino, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of this study, there was slight to no significant changes or toxicity damage occurred in all the treated mice. The detection of liver damage by hepatoxins or drug in the body can be indicated by the level of ALT [ 50 ]. When liver damage happen, additional AST level will be released to the blood as an indicator of a hepatic injury in the host [ 51 ].…”
Section: Discussionmentioning
confidence: 99%